Optimizing Asset Utilization is a Mediating Variable in the Influence of Information Systems, Competence, and Internal Control - Iksan Kusnindar; Suratno; Nurmala Ahmar (Jurnal Akuntansi dan Perpajakan, 2025)
This study aims to investigate the impact of information systems, competencies, and internal controls on asset management effectiveness, as well as the mediating role of asset utilization optimization in this relationship. The research method used an explanatory survey approach. Respondents in this study were 98 employees assigned to state asset management at the Directorate General of State Assets. Quantitative data were collected through a questionnaire survey. The data analysis technique used was Partial Least Squares (PLS) with calculations assisted by the Smart PLS 4.1.1.4 application program.  The results of the study indicate that asset utilization optimization acts as a mediator in the relationship between information systems, human resource competency, and internal control on asset management effectiveness. Based on the bootstrapping results in the PLS-SEM structural model, the specific indirect effect of each independent variable through asset utilization optimization is proven to be significant, while its direct effect remains significant. This finding suggests that the mediation mechanism at work is partial, as evidenced by the coexistence of significant direct and indirect effects on each path. Thus, asset management effectiveness is not only influenced by the quality of information systems, internal competency, and internal control directly, but also by the organization's ability to convert these factors into optimal, productive, and accountable asset utilization practices.